THE MAIN CHARACTER’S STRUGGLE OF ROBERT LOUIS STEVENSON KIDNAPPED - br Barus, Cahaya Mutiara; Ningsih, Ayu Melati (Fakultas Sastra UMN AL Washliyah, 2025)
This study analyzes the forms of struggle of the main character in the novel Kidnapped by Robert Louis Stevenson. Using a qualitative content analysis method with the approach of Badio's struggle theory (2022), this study identifies and classifies the various types of struggles experienced by David Balfour. The results of the study show that there are 28 valid forms of struggle, divided into four main categories: (1) 7 heroic struggles, (2) 11 never-give-up struggles, (3) 2 family-related struggles, and (4) 8 selflessness struggles. Interesting findings show the absence of elements of nationalism-based struggle in the story narrative. This study provides a new perspective on character development through life challenges in classic literary works.